IMPLEMENTATION OF TOTAL QUALITY MANAGEMENT (TQM) IN IMPROVING MANAGERIAL PERFORMANCE IN POST-MERGER SYARIAH BANK INDONESIA - Helmina Ardyanfitri; Wilma Cordelia Izaak (Journal of Economics, Business, and Government Challenges, 2023)
This research aims to analysis of the implementation of Total Quality Management (TQM) at Bank Syariah Indonesia branch office Surabaya Dharmawangsa and analysis of the implementation of Total Quality Management (TQM) in order to improve managerial performance at Bank Syariah Indonesia, branch office Surabaya Dharmawangsa. This study uses a qualitative research method with a descriptive approach. Research data obtained from primary data and secondary data. While the primary data sources are four employees of Bank Syariah Indonesia branch office Surabaya Dharmawangsa with secondary data from various literatures such as books, journals, and articles that are relevant. Data collection techniques used by observation, interview, and documentation. While the data processing technique is done by editing, organizing and analyzing data. The results obtained by researchers are that the application of Total Quality Management (TQM) at Bank Syariah Indonesia branch office Surabaya Dharmawangsa is considered quite good and in line with Total Quality Management (TQM) theory which is a strategy in management that is oriented to customer satisfaction which involves all employees or parts of the company. The application of Total Quality Management (TQM) has relevance to managerial performance at Bank Syariah Indonesia branch office Surabaya Dharmawangsa. This is evidenced by the many aspects that can be linked such as evaluations carried out to improve managerial performance as well as in Total Quality Management (TQM).